1986
DOI: 10.1002/1097-0142(19860215)57:4<875::aid-cncr2820570432>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell tumor of the tendon sheath (nodular tenosynovitis): A study of 207 cases to compare the large joint group with the common digit group

Abstract: Clinicopathologic, enzyme histochemical, and electron microscopic findings in 207 cases (208 lesions) of giant cell tumor of tendon sheath (GCTTS) are presented. The GCTTS could he divided into two groups according to the anatomic location, the first occurring in the digits (digit group, 182 cases) and the second, in the larger joints (large joint group, 25 cases). In the majority of cases of the digit group, the tumor occurred in one of the fingers (158 cases), whereas in the large joint group, the tumor was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
138
0
28

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(170 citation statements)
references
References 18 publications
4
138
0
28
Order By: Relevance
“…Only 37 malignant tenosynovial GCTs have been reported in the literature since 1979, and these are summarized in ►Tables 1-3. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Of these 37 patients, follow-up outcome was known in 30 patients; one patient had died of other causes (DOC). Of the remaining 29 patients, 11 patients died of disease (DOD), 4 patients were living with disease (LWD) and 14 patients had no evidence of disease (NED) since their last treatment, with a follow-up of 6 months to 49 years.…”
Section: Discussionmentioning
confidence: 99%
“…Only 37 malignant tenosynovial GCTs have been reported in the literature since 1979, and these are summarized in ►Tables 1-3. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Of these 37 patients, follow-up outcome was known in 30 patients; one patient had died of other causes (DOC). Of the remaining 29 patients, 11 patients died of disease (DOD), 4 patients were living with disease (LWD) and 14 patients had no evidence of disease (NED) since their last treatment, with a follow-up of 6 months to 49 years.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that this disease is resultant from a lipid metabolism change, inflammation or benign neoplasic process (11) . The potential of this disease being induced by trauma is described; Rodrigues et al found a prevalence of previous trauma in 21% of patients with GCTTS (1,2,5) . The clinical and X-ray-based diagnosis of GCTTS is difficult, because anamnesis, physical examination and X-ray data are unspecific, requiring the establishment of differential diagnoses of potential causes for knee arthralgia.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, a conservative excision with a surrounding rim of normal tissue is adequate. 4,19,24,34,35 Vascular and related tissues…”
Section: Giant Cell Tumor Of Tendon Sheath (Localized Type)mentioning
confidence: 99%